FORMING 4K SKILLS IN STUDENTS WHEN TEACHING THE TOPIC OF ACIDS - Sadikova Umidakhan Bakhtiyar kizi (Research Focus International Scientific Journal, 2025)
This article develops tasks focused on 21st century skills: communication, creative and critical thinking, and collaboration in teaching the topic of acids in chemistry lessons. All chemistry teachers can use them to explain the topic of acids in 7th grade. In the formation of communication skills, tasks are given that link the importance of acids in our daily lives, which serves to increase students’ interest in the lesson.